Nigerian Poetry: A Systemic Functional Approach - Okwudiri Anasiudu (ELS Journal on Interdisciplinary Studies in Humanities, 2024)
Within the vast landscape of Nigerian literature, evolving into three principal literary genres, the critical study of poetry has been somewhat neglected, especially when contrasted with the substantial analysis devoted to drama and novels. This is partially attributed to the language used in poetry, its nature which is steep in semantic indirection and its method of pedagogy which often problematizes its appreciation. This study contributes to the study of poetry by exploring Nigerian poetry within the tenets of M.A.K. Halliday's Systemic Functional Linguistic, and qualitative and descriptive design. The analysis focuses on a selected corpus of written Nigerian poetry in the English language, by Wole Soyinka, Christopher Okigbo, Tanure Ojaide, Odia Ofeimun, Psalms Chinaka, and Obari Gomba, which spans the oeuvres of three distinct generations and serve as exemplars of their respective generations. The study provides valuable insights into the significance of language, the evolution of Nigerian poetry, and its styles and functions. It is supported by tangible examples that showcase various elements, such as cohesion, deviation, and code-mixing. It offers a crucial understanding that the use of English in Nigerian poetry is not just a colonial legacy. It is a choice shaped by postcolonial reality. Its deployment is not incidental but a deliberate act of appropriation, protest, and a call for change. This is by the amplification of the voices of marginalized groups within Nigerian society such that language as a socio-semiotic system is deployed to tackle multifaceted issues that plague Nigerian society. The study submits that there is a nuanced tapestry of ideological and stylistic dialogue that connects and differentiates the first, second, and third generations of Nigerian poets. This intergenerational dialogue highlights a continuum of thematic and aesthetic concerns, with notable shifts reflecting the evolving socio-political landscape of Nigeria.